Bioethics’ virtual teaching, challenges - Rodríguez Yunta, Eduardo; Valdebenito Herrera, Carolina; Lolas Stepke, Fernando (Acta Bioethica, 2008)
The present paper reflects about the new bioethics teaching modality that employs a plarform of virtual reaching. It points our this model’s advantages and difficulties and the challenges it faces in order to reach an effective result of its pedagogical aims. It recommends to employ semipresential learning models or the combination of a mixed bioethics’ virtual teaching: presential and non presential.